Sand Modified with Nanoparticles of Calcium, Aluminum, and CTAB in the Form of Layered Double Hydroxide for Removing of Amoxicillin from Groundwater - H. Ahmed, Zainab A.; Faisal, Ayad A. H. (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The addition of new reactive sites on the surface area of the inert sand, which are represented by layered double hydroxide nanoparticles, is the primary goal of this work, which aims to transform the sand into a reactive material. Cetyltrimethylammonium bromide (CTAB) surfactant is used in the reaction of calcium extracted from solid waste-chicken eggshells with aluminum prepared from the cheapest coagulant-alum. By separating amoxicillin from wastewater, the performance of coated sand named as "sand coated with (Ca/Al-CTAB)-LDH" was evaluated. Measurements demonstrated that pH of 12 from 8, 9, 10, 11, and 12, CTAB dosage of 0.05 g from 0, 0.03, 0.05, and 0.1 g, ratio of Ca/Al of 2 from 1, 2, 3, and 4, and mass of sand of 1 g/50 mL from 0.5, 1, 1.5, 2, and 2.5 g/50 mL are the optimal manufacturing conditions for coated sand to guarantee an antibiotic removal efficiency greater than 80. After planting the LDH nanoparticles, characterization analyses revealed that the generation of a plate-like layer composed of loosely aggregated micrometric plates had significantly altered the structure of sand. Finally, as the sorbent mass increased as well as the flow rate and inlet contaminant concentration (Co) decreased, the longevity of coated sand in the packed column significantly increased. In comparison to the Belter-Cussler-Hu and Yan models, the Thomas-BDST model provides a more accurate simulation of measured breakthrough curves.